2006
DOI: 10.1017/s1743921307006254
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Small Eccentricity in the Spectroscopic Binary System ζ TrA

Abstract: Abstract.The orbital eccentricity of the SB1 system ζ TrA (S.T. F9V, P ∼ 13 d) was found by Skuljan et al. (2004) to be e = 0.01398±0.00019. Lucy (2005) devised a statistical test of the significance of this result, based on the amplitude and phase of the third harmonic in the Fourier analysis of the radial velocity data, and concluded that the non-zero eccentricity measured does not arise from a slightly eccentric Keplerian orbit, but from proximity effects in the binary. He therefore believes a circular orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Such small eccentricities are impossible to obtain from RV measurements alone, due to the small line-profile distortion expected for short-period binaries (e.g., Lucy 2005; Komonjinda et al 2007). Small eccentricities have been measured previously for pulsars, 5 with WD secondaries in particular (e.g., Manchester et al 2005), utilizing the precise timing of the observed radio pulses.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Such small eccentricities are impossible to obtain from RV measurements alone, due to the small line-profile distortion expected for short-period binaries (e.g., Lucy 2005; Komonjinda et al 2007). Small eccentricities have been measured previously for pulsars, 5 with WD secondaries in particular (e.g., Manchester et al 2005), utilizing the precise timing of the observed radio pulses.…”
Section: Summary and Discussionmentioning
confidence: 99%